Excited state dependent electron transfer of a rhenium-dipyridophenazine complex intercalated between the base pairs of DNA: a time-resolved UV-visible and IR absorption investigation into the photophysics of fac-[Re(CO)3(F2dppz)(py)]+ bound to either [poly(dA-dT)]2 or [poly(dG-dC)]2. - KELLY, JOHN MOFFAT (My University, 2011)
The transient species formed following excitation of fac-[Re(CO)3(F2dppz)(py)]+ (F2dppz = 11,12-difluorodipyrido[3,2-a:2?,3?-c]phenazine) bound to double-stranded polynucleotides [poly(dA-dT)]2 or [poly(dG-dC)]2 have been studied by transient visible and infra-red spectroscopy in both the picosecond and nanosecond time domains. The latter technique has been used to monitor both the metal complex and the DNA by monitoring the regions 1900?2100 and 1500?1750 cm-1 respectively. These data provide direct evidence for electron transfer from guanine to the excited state of the metal complex, which proceeds both on a sub-picosecond time scale and with a lifetime of 35 ps, possibly due to the involvement of two excited states. No electron transfer is found for the [poly(dA-dT)]2 complex, although characteristic changes are seen in the DNA-region TRIR consistent with changes in the binding of the bases in the intercalation site upon excitation of the dppz-complex.
PUBLISHED
Keywords: absorption; article; base pairing; chemistry; electron transport; infrared spectrophotometry; quantum theory; time; ultraviolet spectrophotometry; absorption; article; base pairing; chemistry; electron transport; infrared spectrophotometry; quantum theory; time; ultraviolet spectrophotometry